Countries And The Minerals Industry (The National Institute for Occupational Safety and Health (NIOSH), 1981)
U.S. Gold Commission Established. - The President, with the authorization of Congress, has named a gold commission made up of 17 individuals, most of them Government officials, to study U.S. policies related to the role of gold in domestic and international monetary systems and report its findings and recommendations to Congress. U.S. Lead Exposure Ruling. - On June 29, the Supreme Court upheld the Government's right to set lead exposure levels for employees at the workplace. The Court ruled in favor of the Occupational Safety and Health Administration (OSHA) in a challenge by a group that alleged that OSHA had failed to conduct a cost-benefit analysis prior to issuance of the lead standards. It was the Court's contention that Congress did not require such an analysis when it empowered OSHA to establish workplace standards. The petition to the Court was made by the Lead Industries Association Inc., Battery Council International Inc" American Iron and Steel Institute, St. Joe Minerals Corp., and other lead mining and consuming firms.